2023
DOI: 10.1093/hmg/ddac307
|View full text |Cite
|
Sign up to set email alerts
|

Direct evaluation of neuroaxonal degeneration with the causative genes of neurodegenerative diseases in Drosophila using the automated axon quantification system, MeDUsA

Abstract: Drosophila is an excellent model organism for studying human neurodegenerative diseases (NDs). However, there is still almost no experimental system which could directly observe the degeneration of neurons and automatically quantify axonal degeneration. In this study, we created MeDUsA (a ‘method for the quantification of degeneration using fly axons’), a standalone executable computer program based on Python that combines a pre-trained deep-learning masking tool with an axon terminal counting tool. This softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…To assess the functional impact of this novel human gene variant, we engineered transgenic Drosophila lines expressing both wild type and mutant SART1 under the control of a UAS promoter. Our MeDUsA analysis suggested that the variant may confer a gain-of-toxic-function (Nitta et al, 2023). Moreover, we identified heterozygous loss-of-function mutations in DHX9 as potentially causative for a newly characterized neurodevelopmental disorder.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…To assess the functional impact of this novel human gene variant, we engineered transgenic Drosophila lines expressing both wild type and mutant SART1 under the control of a UAS promoter. Our MeDUsA analysis suggested that the variant may confer a gain-of-toxic-function (Nitta et al, 2023). Moreover, we identified heterozygous loss-of-function mutations in DHX9 as potentially causative for a newly characterized neurodevelopmental disorder.…”
Section: Discussionmentioning
confidence: 95%
“…To this end, we performed an RNAi experiment using the GMR-Gal4 driver and evaluated the number of retinal axons projecting to the second optic ganglion medulla (Figure 3A). To compare the number of retinal axon terminals–R7 axons–between genotypes, we used a previously developed automated method, MeDUsA ( me thod for the quantification of d egeneration us ing fly a xons) (Nitta et al, 2023). We have assessed the extent of their reduction from the total axonal terminal count, thereby determining the degree of axonal terminal degeneration (Nitta et al, 2023; Richard et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations